2013
DOI: 10.1371/journal.pone.0060685
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Induced Apoptosis Is BAK-Dependent, but BAX and BIM-Independent in Breast Tumor

Abstract: Paclitaxel (Taxol)-induced cell death requires the intrinsic cell death pathway, but the specific participants and the precise mechanisms are poorly understood. Previous studies indicate that a BH3-only protein BIM (BCL-2 Interacting Mediator of cell death) plays a role in paclitaxel-induced apoptosis. We show here that BIM is dispensable in apoptosis with paclitaxel treatment using bim−/− MEFs (mouse embryonic fibroblasts), the bim−/− mouse breast tumor model, and shRNA-mediated down-regulation of BIM in huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…Taxane agents can stabilize microtubules by interfering with spindle microtubule dynamics, resulting in cell-cycle arrest [6]. Previous results indicated that the BAK and BIM proteins were important in the cytotoxicity of taxane agents in breast and lung cancer cells [31][32][33][34]. However, as these apoptosis-related proteins take part in a complex network [15], it is difficult to predict apoptotic responses by quantifying simple protein expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taxane agents can stabilize microtubules by interfering with spindle microtubule dynamics, resulting in cell-cycle arrest [6]. Previous results indicated that the BAK and BIM proteins were important in the cytotoxicity of taxane agents in breast and lung cancer cells [31][32][33][34]. However, as these apoptosis-related proteins take part in a complex network [15], it is difficult to predict apoptotic responses by quantifying simple protein expression.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer cells from 40 patients enrolled in the UMIN 000000801 Trial [12] and 22 patients enrolled in the UMIN 000002361 Trial were also examined. At the time of analysis, the median followup time was 29.5 months (range, 3.6-96.4 months), and 46.4 % of the patients [32] had died. Thirty patients died of progressive disease, 1 patient died of a brain infarction, and 1 other patient died in a traffic accident.…”
Section: Inhibition Of Bak Expression Causes Resistance To Apoptosis mentioning
confidence: 99%
“…Retroviral infection was performed as previously described [21]. The lentiviral sh-p53, sh-Bax and sh-Bak-expressing constructs were kindly provided by Dr. Harada (Virginia Commonwealth University, Richmond, VA, USA) [22].…”
Section: Rna Interferencementioning
confidence: 99%
“…Human MM cell lines, 29,30 primary MM samples, and Bim knockout mouse embryonic fibroblasts (MEFs) 31 are described in supplemental Materials, available on the Blood Web site. To establish human MM cells adaptively resistant to bortezomib, RPMI8226 and U266 cells were continuously cultured in gradually increasing concentrations of bortezomib (initially 0.5 nM and increasing in stepwise increments of 0.2 nM) to 10 nM or 15 nM, respectively.…”
Section: Cells and Reagentsmentioning
confidence: 99%